SARS-CoV-2 Vaccination in Solid-Organ Transplant Recipients - Maddalena Peghin; Elena Graziano; Paolo Antonio Grossi (Vaccines, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has posed significant global challenges for solid organ transplant (SOT) recipients. Mortality rates of COVID-19 in this patient population remain high, despite new available therapeutic options and Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) vaccination. Priority access to SARS-CoV-2 vaccination for waitlisted candidates and for SOT patients and their family members is recommended since the advantage from vaccination reduces the risk of COVID-19-related complications. However, immunogenicity and efficacy of COVID-19 vaccines are lower in waitlisted candidates and SOT recipients than in the general population. Routine systematic assessment of humoral and cellular immune responses after SARS-CoV-2 vaccination is controversial, although highly recommended for investigation and improvement of knowledge. SOT recipients should continue to adhere to preventive protective measures despite vaccination and may undergo passive antibody prophylaxis. This article seeks to provide an update on SARS-CoV-2 vaccination and preventive measures in SOT recipients based on existing literature and international guidelines.